المدن التراثية: أشكال تثمين وإنقاذ تجهيزاتها العمومية، المدينة العتيقة للعرائش نموذجا - الوكيلي, سلمى (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى رصد أشكال التدخل التي شهدتها المدينة العتيقة للعرائش بغرض الحفاظ على نسيجها العمراني التقليدي وتجهيزاتها العمومية وكذلك اقتراح بعض الوظائف البديلة التي يمكن أن تسهم في إضفاء طابع جديد على هذا النسيج مع مراعاة الحفاظ على العناصر الاصلية للمبني، توصلت الدراسة إلى أن هذه المدينة نالت حظها من تفعيل مجموعة المشاريع بهدف رد الاعتبار للمجال والساكنة بالرغم من أنها جاءت متأخرة قليلا، هذه المشاريع شارك في وضعها وإنزالها فاعلون ومتدخلون متعددون سواء في مجال التراث أو غيره. مما كان وسيكون له دور مهم في تنمية المدينة وخلق وظائف بديلة تهم التجهيزات التي تتواجد في وضعية متدهورة وإعطائها قيمة أكبر وجعلها أكثر ملاءمة لمزاولة وظائف تعود بالنفع على النسيج العتيق للعرائش والساكنة. This study aims at monitoring the forms of intervention that the ancient city of Larache underwent to preserve its traditional urban fabric and public equipment, and propose some substitute jobs that could contribute to give a new character to this fabric. This is done by taking into account the preservation of the original elements of the structure behind. The study’s finding is that this city got its luck from kickstarting a group of projects with the aim of restoring respect to the field and the inhabitants, although it occurred a little late. Multiple actors and interveners participated in the development and implementation of these projects, whether it be with the mindset of leaving a legacy or something else. This has had and will have an important role in the development of the city and the creation of alternative jobs related to the existing equipment in a deteriorating situation, giving it a greater value and making it more suitable for preserving occupations that benefit the ancient fabric of Larache and the inhabitants
The heritage towns: The old medina of Larache as an example of the different types of enhancement and safeguarding of their public facilities
مقال
Keywords: المدينة العتيقة، الحفاظ، النسيج العمراني، التجهيزات العمومية، رد الاعتبار، التراث.